Cultivating an Entrepreneurial Spirit to Increase Economic Independence in Teenagers in Desa Pancaroba - Selie, Marselina; Saputra, Pramana; Erin Everly, Nyshele; Windiati, Cha Cha; Setia Midianti, Anggi; Nopus Aura, Hilda (Mattawang: Jurnal Pengabdian Masyarakat, 2024)
This KKM-PKM program aims to foster the entrepreneurial spirit of Pancaroba Village youth in order to increase their economic independence and creativity. The activities carried out include socialization on marketing strategies, training in making handicrafts from beads, and socialization on the dangers of promiscuity and bullying. The method of implementing this activity consists of planning, implementation, and evaluation stages. The socialization of marketing strategies helped participants understand how to attract customers and utilize e-commerce platforms such as Shopee. Handicraft training activities from beads helped the teenagers to hone their practical skills in making products that can be sold. The socialization of promiscuity and bullying aimed to provide an understanding of the negative impacts that can arise from these two issues. The results showed an increase in skills and awareness of the participants, who are now better prepared to start a business and understand more about the social issues around them. This program is expected to contribute to the sustainable improvement of the village economy through the improvement of human resources quality and youth entrepreneurship.